2011
DOI: 10.1158/1078-0432.ccr-10-2548
|View full text |Cite
|
Sign up to set email alerts
|

Combined Promoter Methylation Analysis of CADM1 and MAL: An Objective Triage Tool for High-Risk Human Papillomavirus DNA–Positive Women

Abstract: Purpose: Screening women for high-grade cervical intraepithelial neoplasia or cervical cancer (CIN3 þ ) by high-risk human papillomavirus (hrHPV) testing has as side-effect the detection of hrHPV-positive women without clinically relevant lesions. Here, we developed an objective assay assessing the methylation status of the promoter regions of CADM1 and MAL to triage hrHPV-positive women for CIN3 þ .Experimental Design: In a training set (51 women with CIN3 þ and 224 without CIN2 þ ), panels consisting of one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
195
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(205 citation statements)
references
References 37 publications
8
195
1
1
Order By: Relevance
“…Moreover, prior knowledge of hrHPV-positivity influences cytology reading, which may result in an increase of false-positive referrals with simultaneously higher costs for the healthcare system [4749]. Recent clinical validation studies in screening populations have shown that DNA methylation markers provide a good alternative for cytology [14,5054]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior knowledge of hrHPV-positivity influences cytology reading, which may result in an increase of false-positive referrals with simultaneously higher costs for the healthcare system [4749]. Recent clinical validation studies in screening populations have shown that DNA methylation markers provide a good alternative for cytology [14,5054]. …”
Section: Discussionmentioning
confidence: 99%
“…Of 1,040 HPV‐positive women, sufficient left‐over material of baseline cervical scrapes was available and valid FAM19A4/mir124‐2 methylation test results were obtained. DNA from cervical scrapes was isolated using the Nucleo‐Spin 96 Tissue kit (Macherey‐Nagel, Duren, Germany) and a Microlab Star robotic system (Hamilton, Planegg, Germany) according to manufacturers’ protocol 32. Extracted DNA was subjected to bisulphite treatment using the EZ DNA Methylation Kit (Zymo Research, Irvine, CA) as described previously 33, 34.…”
Section: Methodsmentioning
confidence: 99%
“…17 The isolated DNA was subjected to general primers 5+/6+ PCR-enzyme immunoassay (GP5+/6+; Diassay, The Netherlands). 18 A microsphere bead-based assay (Luminex) 19 was used for genotyping of the high-risk …”
Section: Hpv Testing and Genotypingmentioning
confidence: 99%